Efeito do déficit de água no aproveitamento do nitrogênio - 15n na cultura do trigo - Boaretto, Antônio Enedi [UNESP]; Neptune, André Martin Louis; Patella, José Francisco (Universidade de São Paulo (USP), Escola Superior de Agricultura, 1982)
Três fontes de nitrogênio - 15n foram utilizadas: sulfato de amônio, nitrato de amônio e uréia. Elas foram aplicadas no plantio de dois modos: a lanço e a seguir incorporadas ao solo, ou no sulco de plantio. Determinou-se a eficiência de utilização do nitrogênio - 15n aplicado no plantio e no perfilhamento, sendo respectivamente, em media 14 e 13% do nitrogênio aplicado e utilizados pelo trigo. Obtiveram-se valores de 16 e 12% de eficiência do nitrogênio - 15n aplicado no sulco de plantio ou a lanço e a seguir incorporado ao solo, respectivamente.

This paper deals with a study of the efficiency of three nitrogen-15N fertilizers: ammonium sulphate, urea, and ammonium nitrate on wheat crops. The fertilizers were applied by throwing and then incorporated to the soil or in the furrows, at the rate of 120 kg N/ha, half at sowing and half at sowing and half by throwing at the tillering stage. The results were as follows: all fertilizers gave similar effects in straw and grain yields, in the percentage of nitrogen derived from the fertilizers and percentage of fertilizer nitrogen utilized. When the nitrogen fertilizers were applied along the seed rows (5 cm apart and 2 cm deep) it was observed higher values in the nitrogen contents of the grains and in the efficiency of the fertilizers. The mean of all results indicated that 23% of the nitrogen applied was recovered by the wheat plants.
Effect of water deficiency in the utilization of nitrogen (15n) by wheat crops